Zinc battery negative electrode and zinc battery
The integration of zinc, sorbitan compounds, and sugar alcohol compounds with additives in the negative electrode of zinc batteries effectively prevents dendrite formation, enhancing their life performance and cycle stability.
Patent Information
- Application Number
- JP2024080243
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-19
- Filing Date
- 2024-05-16
- Publication Date
- 2025-01-07
AI Technical Summary
Zinc batteries face issues with dendrite formation leading to short circuits, which degrade their life performance, and existing solutions do not adequately address this problem.
Incorporating a negative electrode with a current collector and a material containing zinc, sorbitan compounds, and sugar alcohol compounds, along with additives like polyoxyalkylene sorbitan fatty acid esters, to prevent zinc hydroxide dissolution and dendrite growth.
The proposed electrode design significantly enhances the life performance of zinc batteries by suppressing dendrite formation and maintaining structural integrity, resulting in improved cycle stability.
Smart Images

Figure 2025000554000001 
Figure 2025000554000002 
Figure 2025000554000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode for a zinc battery, a zinc battery, and the like. [Background technology]
[0002] Known zinc batteries include nickel-zinc batteries, air-zinc batteries, and silver-zinc batteries. For example, nickel-zinc batteries are aqueous batteries that use an aqueous electrolyte such as an aqueous potassium hydroxide solution, and therefore are highly safe. In addition, the combination of zinc electrodes and nickel electrodes is known to provide a high electromotive force for an aqueous battery. Furthermore, nickel-zinc batteries have excellent input / output performance and low cost, and therefore their applicability to industrial applications (e.g., backup power sources, etc.) and automotive applications (e.g., hybrid vehicles, etc.) is being considered.
[0003] The charge and discharge reactions of a nickel-zinc battery proceed, for example, according to the following formula (discharge reaction: to the right, charge reaction: to the left). (Positive electrode)2NiOOH+2H2O+2e - → 2Ni(OH)2+2OH - (Negative electrode) Zn+2OH - → Zn(OH)2+2e -
[0004] As shown in the above formula, in zinc batteries, zinc hydroxide (Zn(OH)2) is produced by the discharge reaction. Zinc hydroxide is soluble in the electrolyte, and when zinc hydroxide dissolves in the electrolyte, it becomes zinc tetrahydroxide ions ([Zn(OH)4] 2-) diffuses into the electrolyte. As a result, the negative electrode undergoes a morphological change (deformation) and the distribution of the charging current becomes uneven, causing zinc to precipitate locally on the negative electrode, resulting in the formation of dendrites (branched crystals). In conventional zinc batteries, when dendrites grow due to repeated charging and discharging, the dendrites may penetrate the separator and cause a short circuit. For this reason, various attempts have been made to prevent such short circuits caused by dendrites and to improve the life performance. For example, the following Patent Document 1 discloses a nickel-zinc battery in which a nonwoven fabric made of nylon, polypropylene, or the like is nickel-plated and the nonwoven fabric is interposed between the positive and negative electrodes. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 58-126665 Summary of the Invention [Problem to be solved by the invention]
[0006] In zinc batteries such as nickel-zinc batteries, there is a demand for further improvement in life performance, and there is a demand for the development of new technologies for improving life performance.
[0007] An object of the present disclosure is to provide a zinc battery negative electrode capable of obtaining excellent life performance in a zinc battery.An object of the present disclosure is to provide a zinc battery including the zinc battery negative electrode. [Means for solving the problem]
[0008] Some aspects of the present disclosure relate to the following items [1] to [7] etc. [1] A negative electrode for a zinc battery, comprising: a negative electrode current collector; and a negative electrode material supported on the negative electrode current collector, the negative electrode material containing a negative electrode active material containing zinc and at least one additive selected from the group consisting of sorbitan compounds and sugar alcohol compounds. [2] The negative electrode for a zinc battery according to [1], wherein the additive comprises a polyoxyalkylene sorbitan fatty acid ester. [3] The negative electrode for a zinc battery according to [2], wherein the polyoxyalkylene sorbitan fatty acid ester has an HLB value of 9.0 or more. [4] The negative electrode for a zinc battery according to any one of [1] to [3], wherein the additive contains sorbitan. [5] The negative electrode for a zinc battery according to any one of [1] to [4], wherein the additive contains a sugar alcohol. [6] The negative electrode for a zinc battery according to any one of [1] to [5], wherein the content of the additive is 0.1 to 10 parts by mass per 100 parts by mass of the negative electrode active material. [7] A zinc battery comprising the zinc battery negative electrode according to any one of [1] to [6] and a positive electrode. Effect of the Invention
[0009] According to one aspect of the present disclosure, it is possible to provide a zinc battery negative electrode capable of obtaining excellent life performance in a zinc battery. According to another aspect of the present disclosure, it is possible to provide a zinc battery including the zinc battery negative electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In this specification, the numerical range indicated by "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. The numerical range "A or more" means a range exceeding A and A. The numerical range "A or less" means a range less than A and A. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of a numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types. In this specification, the amount of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. In this specification, the term "film" or "layer" includes a structure having a shape formed over the entire surface as well as a structure having a shape formed on a part of the surface when observed in a plan view. In this specification, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended effect of the process is achieved. The term "hydroxyl group" does not include an OH structure contained in a carboxy group.
[0011] Hereinafter, embodiments of the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments, and can be modified in various ways within the scope of the present disclosure.
[0012] The zinc battery according to this embodiment includes a negative electrode (negative electrode for zinc batteries, e.g., a negative electrode plate) and a positive electrode (positive electrode for zinc batteries, e.g., a positive electrode plate). The zinc battery according to this embodiment may have an electrode group consisting of a plurality of negative electrodes and a plurality of positive electrodes. The negative electrodes and positive electrodes are alternately stacked, for example, with a separator between them, with the main surface of the negative electrode and the main surface of the positive electrode facing each other. The electrode group may have a negative electrode, a positive electrode, and a separator disposed between the negative electrode and the positive electrode. In this case, the negative electrode and the positive electrode face each other through the separator. The plurality of negative electrodes and the plurality of positive electrodes may be connected to each other, for example, by a strap.
[0013] Examples of the zinc battery (e.g., zinc secondary battery) according to the present embodiment include a nickel-zinc battery (e.g., nickel-zinc secondary battery) whose positive electrode is a nickel electrode; an air-zinc battery (e.g., air-zinc secondary battery) whose positive electrode is an air electrode; and a silver-zinc battery (e.g., silver-zinc secondary battery) whose positive electrode is a silver oxide electrode. The basic configuration of the zinc battery according to the present embodiment can be the same as that of a conventional zinc battery. The zinc battery according to the present embodiment may be either before or after chemical formation.
[0014] The negative electrode (negative electrode for zinc battery) has a negative electrode current collector and a negative electrode material supported on the negative electrode current collector. The negative electrode material contains a negative electrode active material containing zinc and at least one additive selected from the group consisting of sorbitan compounds and sugar alcohol compounds (hereinafter referred to as "additive A"). The positive electrode has a positive electrode current collector and a positive electrode material supported on the positive electrode current collector. Each of the negative electrode and the positive electrode may be either before or after chemical formation.
[0015] According to the negative electrode of this embodiment, excellent life performance can be obtained in a zinc battery because the negative electrode material contains additive A. According to one aspect of the negative electrode of this embodiment, a capacity retention rate of, for example, 30% or more (preferably, 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, etc.) can be obtained in the evaluation described in the examples described later.
[0016] The reason why excellent life performance is obtained is not clear, but according to the knowledge of the present inventor, it is presumed as follows. However, the reason is not limited to the following. That is, in the negative electrode of a zinc battery, zinc oxide in the negative electrode material comes into contact with the electrolyte, and tetrahydroxide zincate ions ([Zn(OH)4] 2- ) diffuses into the electrolyte, and zinc is locally precipitated, causing various problems such as morphology changes. In contrast, in this embodiment, additive A suppresses contact between the zinc oxide of the negative electrode material and the electrolyte, preventing the diffusion of zinc tetrahydroxide ions into the electrolyte and the local precipitation of zinc. This makes it possible to suppress morphology changes in the negative electrode, thereby achieving excellent life performance.
[0017] Hereinafter, the zinc battery according to this embodiment will be described using a nickel-zinc battery as an example.
[0018] The current collector (negative electrode current collector or positive electrode current collector) constitutes a conductive path for current from the electrode material (negative electrode material or positive electrode material). The current collector has, for example, a flat plate shape, a sheet shape, or the like. The current collector may be a three-dimensional mesh-structured current collector made of foamed metal, expanded metal, punched metal, felt-like material of metal fiber, or the like.
[0019] Examples of materials constituting the current collector include platinum; nickel (foamed nickel, etc.); and metal materials (copper, brass, steel, etc.) plated with a metal such as tin or nickel.
[0020] The electrode material (negative electrode material or positive electrode material) may be a layered electrode material layer (negative electrode material layer or positive electrode material layer). For example, the electrode material layer may be formed on a current collector, and when the current collector has a three-dimensional mesh structure, the electrode material may be filled between the meshes of the current collector to form the electrode material layer.
[0021] The negative electrode material contains a negative electrode active material containing zinc. Examples of the negative electrode active material include metallic zinc, zinc oxide, and zinc hydroxide. For example, the negative electrode material contains metallic zinc in a fully charged state, and contains zinc oxide and zinc hydroxide in an end-of-discharge state. The negative electrode active material may be, for example, in a particulate form, and may contain metallic zinc particles, zinc oxide particles, zinc hydroxide particles, and the like.
[0022] The particulate negative electrode active material (e.g., particulate negative electrode active material containing zinc oxide) may include primary particles and may include secondary particles. The shape of the primary particles may be a hexagonal column, a plate (e.g., a hexagonal plate), or the like. The shape of the secondary particles may be a plate-like accumulated sphere.
[0023] The particle diameter (primary particle diameter or secondary particle diameter. For example, particle diameter at the end of discharge) of the particulate negative electrode active material may be in the following range. From the viewpoint of easily obtaining excellent life performance, the particle diameter may be 100 nm or more, 200 nm or more, 300 nm or more, 400 nm or more, 500 nm or more, 600 nm or more, 700 nm or more, 800 nm or more, 900 nm or more, or 1000 nm or more. From the viewpoint of easily obtaining excellent life performance, the particle diameter may be 2000 nm or less, 1500 nm or less, 1200 nm or less, or 1000 nm or less. The particle diameter may be 800 nm or less, or 600 nm or less. From these viewpoints, the particle diameter may be 100 to 2000 nm, 300 to 1500 nm, or 500 to 1200 nm. The particle diameter may be a number average particle diameter. The particle size may be the average value of the maximum sizes of 100 particles observed with a scanning electron microscope.
[0024] The BET specific surface area of the negative electrode active material (for example, the BET specific surface area at the end of discharge) may be in the following range. From the viewpoint of easily obtaining excellent life performance, the BET specific surface area is 0.1 m 2 / g or more, 0.5m 2 / g or more, 1.0m 2 / g or more, 1.5m 2 / g or more, 1.8m 2 / g or more, 2.0m 2 / g or more, 2.2m 2 / g or more, 2.5m2 / g or more, 3.0m 2 / g or more, 4.0m 2 / g or more, 5.0m 2 / g or more, 6.0m 2 / g or more, 7.0m 2 / g or more, or 8.0m 2 The BET specific surface area may be 15 m / g or more from the viewpoint of easily obtaining excellent life performance. 2 / g or less, 12m 2 / g or less, 10m 2 / g or less, or 9.0m 2 / g or less. The BET specific surface area may be 8.0 m 2 / g or less, 5.0m 2 / g or less, 4.0m 2 / g or less, or 3.0m 2 From these viewpoints, the BET specific surface area may be 0.1 to 15 m 2 / g or less, 1.0~10m 2 / g or less, or 2.0 to 9.0 m 2 The BET specific surface area of the negative electrode active material can be measured by a BET single-point method using nitrogen gas in accordance with JIS Z 8803:2013.
[0025] The tap density of the negative electrode active material (for example, the tap density at the end of discharge) may be in the following range. From the viewpoint of easily obtaining excellent life performance, the tap density is 0.10 g / cm 3 More than 0.20g / cm 3 More than 0.30g / cm 3 More than 0.40g / cm 3 More than 0.50g / cm 3 More than 0.60g / cm 3 More than 0.70g / cm 3 or more than 0.71 g / cm 3 The tap density is preferably 3.0 g / cm3 from the viewpoint of easily obtaining excellent life performance. 3 Below 2.0g / cm 3 Below 1.0g / cm 3 Below, 0.90g / cm 3 Below 0.80g / cm 3Below 0.75g / cm 3 Less than or equal to 0.73 g / cm 3 The tap density may be 0.71 g / cm or less. 3 Less than or equal to 0.70g / cm 3 From these viewpoints, the tap density may be 0.1 to 3.0 g / cm 3 , 0.30~1.0g / cm 3 , or 0.50 to 0.80 g / cm 3 The tap density of the negative electrode active material can be measured in accordance with JIS Z 2512:2012.
[0026] The content of the negative electrode active material may be in the following ranges based on the total mass of the negative electrode material from the viewpoint of easily obtaining excellent life performance. The content of the negative electrode active material may be 50 mass% or more, 70 mass% or more, 75 mass% or more, 80 mass% or more, 85 mass% or more, or 90 mass% or more. The content of the negative electrode active material may be 99 mass% or less, 98 mass% or less, 96 mass% or less, 95 mass% or less, 93 mass% or less, or 92 mass% or less. From these viewpoints, the content of the negative electrode active material may be 50 to 99 mass%, 70 to 99 mass%, 80 to 99 mass%, 90 to 99 mass%, 50 to 98 mass%, 70 to 98 mass%, 80 to 98 mass%, 90 to 98 mass%, 50 to 95 mass%, 70 to 95 mass%, 80 to 95 mass%, or 90 to 95 mass%.
[0027] From the viewpoint of obtaining an excellent life performance, the negative electrode material contains at least one additive A selected from the group consisting of a sorbitan compound and a sugar alcohol compound. The sorbitan compound is at least one selected from the group consisting of sorbitan and a sorbitan derivative. The sugar alcohol compound is at least one selected from the group consisting of a sugar alcohol and a sugar alcohol derivative.
[0028] Additive A may contain at least one selected from the group consisting of sorbitan and sorbitan derivatives, or may contain sorbitan or a sorbitan derivative, from the viewpoint of easily obtaining excellent life performance. Examples of sorbitan derivatives include sorbitan fatty acid esters. The sorbitan fatty acid ester may be a polyoxyalkylene sorbitan fatty acid ester having a polyoxyalkylene chain, or may be a sorbitan fatty acid ester not having a polyoxyalkylene chain. Examples of the polyoxyalkylene chain in the polyoxyalkylene sorbitan fatty acid ester include a polyoxyethylene chain and a polyoxypropylene chain. The polyoxyalkylene sorbitan fatty acid ester may have a polyoxyethylene chain, from the viewpoint of easily obtaining excellent life performance.
[0029] From the viewpoint of easily obtaining excellent life performance, additive A may contain a polyoxyalkylene sorbitan fatty acid ester, and may contain at least one selected from the group consisting of polyoxyalkylene sorbitan monofatty acid esters, polyoxyalkylene sorbitan difatty acid esters, and polyoxyalkylene sorbitan trifatty acid esters, or may contain a polyoxyethylene sorbitan fatty acid ester, and may contain at least one selected from the group consisting of polyoxyethylene sorbitan monofatty acid esters, polyoxyethylene sorbitan difatty acid esters, and polyoxyethylene sorbitan trifatty acid esters.
[0030] The number of moles of alkylene oxide added in the polyoxyalkylene sorbitan fatty acid ester may be in the following ranges from the viewpoint of easily obtaining excellent life performance. The number of moles added may be 10 or more, 12 or more, 14 or more, 15 or more, 16 or more, 18 or more, 19 or more, or 20 or more. The number of moles added may be 30 or less, 28 or less, 26 or less, 25 or less, 24 or less, 22 or less, 21 or less, or 20 or less. From these viewpoints, the number of moles added may be 10 to 30, 15 to 30, 18 to 30, 10 to 25, 15 to 25, 18 to 25, 10 to 22, 15 to 22, or 18 to 22.
[0031] The number of carbon atoms in the fatty acid (fatty acid that gives a sorbitan fatty acid ester (for example, a polyoxyalkylene sorbitan fatty acid ester); the same applies below) of the sorbitan fatty acid ester (for example, a polyoxyalkylene sorbitan fatty acid ester) may be within the following ranges from the viewpoint of easily obtaining excellent life performance. The number of carbon atoms may be 8 or more, 10 or more, 12 or more, 14 or more, 16 or more, or 18 or more. The number of carbon atoms may be 30 or less, 28 or less, 26 or less, 24 or less, 22 or less, 20 or less, 18 or less, 16 or less, 14 or less, or 12 or less. From these viewpoints, the number of carbon atoms may be 8 to 30, 8 to 24, 8 to 20, 8 to 18, 8 to 12, 12 to 30, 12 to 24, 12 to 20, 12 to 18, 16 to 30, 16 to 24, 16 to 20, or 16 to 18. When a sorbitan fatty acid ester (e.g., a polyoxyalkylene sorbitan fatty acid ester) is a compound derived from multiple types of fatty acids, the number of carbon atoms of the fatty acids in the sorbitan fatty acid ester (e.g., a polyoxyalkylene sorbitan fatty acid ester) may be the average value of the carbon numbers of the fatty acids.
[0032] The ratio of the carbon number of the fatty acid of the polyoxyalkylene sorbitan fatty acid ester to the HLB value of the polyoxyalkylene sorbitan fatty acid ester described below (carbon number of fatty acid / HLB value) may be in the following range from the viewpoint of easily obtaining excellent life performance. The ratio may be 2.00 or less, 1.80 or less, less than 1.80, 1.75 or less, 1.70 or less, 1.60 or less, 1.50 or less, 1.40 or less, 1.30 or less, 1.25 or less, 1.20 or less, 1.15 or less, 1.10 or less, 1.05 or less, 1.00 or less, 0.90 or less, or 0.80 or less. The ratio may be 0.50 or more, 0.60 or more, 0.70 or more, 0.80 or more, 0.90 or more, 1.00 or more, 1.05 or more, 1.10 or more, 1.15 or more, 1.20 or more, 1.25 or more, 1.30 or more, 1.40 or more, 1.50 or more, or 1.60 or more. From these viewpoints, the ratio may be 0.50 to 2.00, 1.00 to 2.00, 1.10 to 2.00, 0.50 or more and less than 1.80, 1.00 or more and less than 1.80, 1.10 or more and less than 1.80, 0.50 to 1.50, 1.00 to 1.50, or 1.10 to 1.50.
[0033] The fatty acid of the sorbitan fatty acid ester (e.g., polyoxyalkylene sorbitan fatty acid ester) may be a saturated fatty acid or an unsaturated fatty acid. Examples of the fatty acid of the sorbitan fatty acid ester (e.g., polyoxyalkylene sorbitan fatty acid ester) include caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, arachidic acid, and behenic acid. From the viewpoint of easily obtaining excellent life performance, the polyoxyalkylene sorbitan fatty acid ester may contain a polyoxyalkylene sorbitan unsaturated fatty acid ester or may contain a polyoxyethylene sorbitan oleic acid ester.
[0034] Examples of sorbitan derivatives include sorbitan monolaurate, sorbitan monomyristate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan dilaurate, sorbitan dimyristate, sorbitan dipalmitate, sorbitan distearate, sorbitan dioleate, sorbitan trilaurate, sorbitan trimyristate, sorbitan tripalmitate, sorbitan tristearate, sorbitan trioleate, polyoxyalkylene sorbitan monolaurate (e.g., polyoxyethylene sorbitan monolaurate), polyoxyalkylene sorbitan monomyristate, polyoxyalkylene sorbitan monopalmitate (e.g., polyoxyethylene sorbitan monopalmitate), polyoxyalkylene sorbitan monostearate (e.g., polyoxyethylene sorbitan monostearate), polyoxyalkylene sorbitan monooleate (e.g., polyoxyethylene sorbitan monooleate), polyoxyalkylene sorbitan dilaurate, polyoxyalkylene sorbitan dimyristate, polyoxyalkylene sorbitan dipalmitate, polyoxyalkylene sorbitan distearate, polyoxyalkylene sorbitan dioleate, polyoxyalkylene sorbitan trilaurate, polyoxyalkylene sorbitan trimyristate, polyoxyalkylene sorbitan tripalmitate, polyoxyalkylene sorbitan tristearate (e.g., polyoxyethylene sorbitan tristearate), polyoxyalkylene sorbitan trioleate (e.g., polyoxyethylene sorbitan trioleate), and the like. Examples of polyoxyalkylene sorbitan fatty acid esters include polysorbate 20, polysorbate 40, polysorbate 60, polysorbate 65, polysorbate 80, polysorbate 85, and the like.From the viewpoint of easily obtaining excellent life performance, additive A may contain at least one selected from the group consisting of polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, and polyoxyethylene sorbitan tristearate, may contain polyoxyethylene sorbitan monooleate, may contain at least one selected from the group consisting of polysorbate 20, polysorbate 60, polysorbate 65, and polysorbate 80, and may contain polysorbate 80.
[0035] The polyoxyalkylene sorbitan fatty acid ester may contain a compound represented by the following general formula (1) in order to easily obtain excellent life performance.
[0036] [ka] [In formula (1), w, x, y, and z each independently represent an integer of 0 or more, and at least one of w, x, y, and z represents an integer of 1 or more. 1 , L 2 , L 3 and L 4 R each independently represents a hydrocarbon group. 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom or a group represented by the following general formula (2), R 1 , R 2 , R 3 and R 4 At least one of the groups is a group represented by general formula (2).
[0037] [ka] [In formula (2), R 5 represents a hydrocarbon group, and * represents a bond.
[0038] In formula (1), when w is 2 or more, there are multiple L1 may be the same or different. When x is 2 or more, a plurality of L 2 may be the same or different. When y is 2 or more, a plurality of L 3 may be the same or different. When z is 2 or more, a plurality of L 4 may be the same or different. [-OL 1 -], [-OL 2 -], [-OL 3 -] or [-OL 4 The structural units represented by R may be present randomly or may form blocks. 1 , R 2 , R 3 and R 4 When more than one of R 5 may be the same as or different from each other.
[0039] w, x, y, and z each represent the number of structural units, and w+x+y+z may be within the above-mentioned numerical range (e.g., 10 to 30) as the number of moles of alkylene oxide added in the polyoxyalkylene sorbitan fatty acid ester.
[0040] L 1 , L 2 , L 3 and L 4 Examples of the hydrocarbon group include alkylene groups such as an ethylene group and a propylene group.
[0041] R 5 The hydrocarbon group of R may be a saturated hydrocarbon group or an unsaturated hydrocarbon group. 5 Examples of the hydrocarbon group of R include an alkyl group and an alkenyl group. 5 The hydrocarbon group of may be linear or branched. The number of carbon atoms in the group represented by formula (2) (the number of carbon atoms in the carbonyl group and R 5The total number of carbon atoms of the hydrocarbon group (including the carbon number of the hydrocarbon group) may be within the numerical ranges (eg, 8 to 30) mentioned above as the carbon number of the fatty acid of the sorbitan fatty acid ester (eg, polyoxyalkylene sorbitan fatty acid ester).
[0042] The HLB value of the polyoxyalkylene sorbitan fatty acid ester may be in the following range. The HLB value may be 9.0 or more, 9.5 or more, 10.0 or more, 10.5 or more, 11.0 or more, 11.5 or more, 12.0 or more, 12.5 or more, or 13.0 or more, from the viewpoint that excellent life performance is easily obtained by sufficiently dispersing in a solvent during electrode production and obtaining a uniform electrode. The HLB value may be 20.0 or less, 19.5 or less, 19.0 or less, 18.5 or less, 18.0 or less, 17.5 or less, 17.0 or less, 16.5 or less, 16.0 or less, or 15.7 or less, from the viewpoint that excellent life performance is easily obtained by the polyoxyalkylene sorbitan fatty acid ester being less likely to be eluted in the electrolyte. From these viewpoints, the HLB value may be 9.0 to 20.0, 9.0 to 18.0, 9.0 to 16.0, 10.0 to 20.0, 10.0 to 18.0, 10.0 to 16.0, 12.0 to 20.0, 12.0 to 18.0, or 12.0 to 16.0. The HLB value can be calculated by the Griffin method represented by the following formula. HLB value = 20 x (total molecular weight of hydrophilic group portion) / (total molecular weight)
[0043] From the viewpoint of easily obtaining excellent life performance, the additive A may contain at least one selected from the group consisting of sugar alcohols and sugar alcohol derivatives, may contain sugar alcohol, and may contain sugar alcohol derivatives. Examples of sugar alcohols include sorbitol, erythritol, maltitol, pentaerythritol, arabitol, ribitol, xylitol, dulcitol, mannitol, etc. Examples of sugar alcohol derivatives include sugar alcohol esters, etc.
[0044] The number of carbon atoms in the sugar alcohol compound may be within the following ranges from the viewpoint of easily obtaining excellent life performance. The number of carbon atoms may be 3 or more, 4 or more, 5 or more, 6 or more, 8 or more, 10 or more, or 12 or more. The number of carbon atoms may be 14 or less, 12 or less, 10 or less, 8 or less, 6 or less, 5 or less, or 4 or less. From these viewpoints, the number of carbon atoms may be 3 to 14, 4 to 14, 6 to 14, 8 to 14, 3 to 12, 4 to 12, 6 to 12, 8 to 12, 3 to 8, 4 to 8, 6 to 8, 3 to 6, 4 to 6, or 3 to 4.
[0045] The number of hydroxyl groups in the sugar alcohol compound may be within the following ranges from the viewpoint of easily obtaining excellent life performance. The number of hydroxyl groups may be 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, or 9 or more. The number of hydroxyl groups may be 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, or 4 or less. From these viewpoints, the number of hydroxyl groups may be 3 to 10, 4 to 10, 6 to 10, 8 to 10, 3 to 9, 4 to 9, 6 to 9, 8 to 9, 3 to 8, 4 to 8, 6 to 8, 3 to 6, 4 to 6, or 3 to 4.
[0046] The content C1 of additive A, sorbitan compound, sorbitan, sorbitan derivative, polyoxyalkylene sorbitan fatty acid ester, sugar alcohol compound, or sugar alcohol may be in the following range relative to 100 parts by mass of the negative electrode active material. From the viewpoint of easily obtaining excellent life performance, the content C1 may be more than 0 parts by mass, 0.01 parts by mass or more, 0.05 parts by mass or more, 0.1 parts by mass or more, 0.3 parts by mass or more, 0.5 parts by mass or more, 0.6 parts by mass or more, 0.8 parts by mass or more, 0.9 parts by mass or more, 1.0 parts by mass or more, 1.5 parts by mass or more, 2.0 parts by mass or more, or 2.4 parts by mass or more. From the viewpoint of easily obtaining excellent high-rate discharge performance, the content C1 may be 10 parts by mass or less, less than 10 parts by mass, 9.0 parts by mass or less, 8.0 parts by mass or less, 5.0 parts by mass or less, 3.0 parts by mass or less, 2.5 parts by mass or less, 2.0 parts by mass or less, 1.5 parts by mass or less, 1.0 parts by mass or less, 0.9 parts by mass or less, 0.8 parts by mass or less, 0.6 parts by mass or less, or 0.5 parts by mass or less. From these viewpoints, the content C1 may be more than 0 parts by mass and not more than 10 parts by mass, more than 0 parts by mass and not more than 10 parts by mass, more than 0 parts by mass and not more than 5.0 parts by mass, more than 0 parts by mass and not more than 3.0 parts by mass, more than 0 parts by mass and not more than 2.0 parts by mass, 0.1 to 10 parts by mass, 0.1 parts by mass or more and less than 10 parts by mass, 0.1 to 5.0 parts by mass, 0.1 to 3.0 parts by mass, 0.1 to 2.0 parts by mass, 0.5 to 10 parts by mass, 0.5 parts by mass or more and less than 10 parts by mass, 0.5 to 5.0 parts by mass, 0.5 to 3.0 parts by mass, 0.5 to 2.0 parts by mass, 0.6 to 2.0 parts by mass, 2.0 to 10 parts by mass, 2.0 parts by mass or more and less than 10 parts by mass, 2.0 to 5.0 parts by mass, or 2.0 to 3.0 parts by mass.
[0047] The content C2 of the additive A, the sorbitan compound, the sorbitan, the sorbitan derivative, the polyoxyalkylene sorbitan fatty acid ester, the sugar alcohol compound, or the sugar alcohol may be in the following range based on the total mass of the negative electrode material. From the viewpoint of easily obtaining excellent life performance, the content C2 may be more than 0 mass%, 0.01 mass% or more, 0.05 mass% or more, 0.1 mass% or more, 0.3 mass% or more, 0.5 mass% or more, 0.6 mass% or more, 0.8 mass% or more, 0.9 mass% or more, 1.0 mass% or more, 1.5 mass% or more, or 2.0 mass% or more. From the viewpoint of easily obtaining excellent high-rate discharge performance, the content C2 may be 10 mass% or less, less than 10 mass%, 9.0 mass% or less, 8.0 mass% or less, 5.0 mass% or less, 3.0 mass% or less, 2.8 mass% or less, 2.5 mass% or less, 2.0 mass% or less, 1.5 mass% or less, 1.0 mass% or less, 0.9 mass% or less, 0.8 mass% or less, or 0.6 mass% or less. From these viewpoints, the content C2 is more than 0 mass% and less than 10 mass%, more than 0 mass% and less than 10 mass%, more than 0 mass% and less than 5.0 mass%, more than 0 mass% and less than 3.0 mass%, more than 0 mass% and less than 2.0 mass%, 0.1-10 mass%, 0.1 mass% or more and less than 10 mass%, 0.1-5.0 mass%, 0.1-3.0 mass%, 0.1 It may be ~2.0 mass%, 0.5-10 mass%, 0.5-5.0 mass%, 0.5-3.0 mass%, 0.5-2.0 mass%, 0.6-2.0 mass%, 2.0-10 mass%, 2.0 mass% or more and less than 10 mass%, 2.0-5.0 mass%, or 2.0-3.0 mass%.
[0048] The negative electrode material may contain additives other than the negative electrode active material and additive A. Examples of the additives include a binding agent (binder) and a conductive agent.
[0049] Examples of the binder include polyvinyl alcohol (PVA), polytetrafluoroethylene, hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC), polyethylene oxide, polyethylene, polypropylene, etc. The content of the binder may be 0.5 to 10 parts by mass with respect to 100 parts by mass of the negative electrode active material.
[0050] Examples of the conductive agent include metal compounds and carbon materials. Examples of the metal compounds include metal oxides having a higher reduction potential than zinc, such as indium oxide, bismuth oxide, lead oxide, cadmium oxide, and thallium oxide; metal oxides having high wettability, such as titanium oxide, aluminum oxide, and silicon oxide; calcium compounds, such as calcium oxide and calcium hydroxide; and fluorine compounds, such as potassium fluoride and calcium fluoride. The content of the metal compounds may be 0.5 to 10 parts by mass relative to 100 parts by mass of the negative electrode active material. Examples of the carbon materials include acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black. The content of the carbon materials may be 1 to 20 parts by mass relative to 100 parts by mass of the negative electrode active material.
[0051] The positive electrode material contains a positive electrode active material. The positive electrode active material may contain nickel. Examples of the positive electrode active material include nickel oxyhydroxide (NiOOH) and nickel hydroxide. The positive electrode material contains, for example, nickel oxyhydroxide in a fully charged state and nickel hydroxide in an end-of-discharge state. The content of the positive electrode active material may be 50 to 99 mass% based on the total mass of the positive electrode material.
[0052] The positive electrode material may contain additives other than the positive electrode active material. Examples of additives include a binder, a conductive agent, an expansion inhibitor, and a rare earth metal compound (e.g., yttrium oxide). Examples of the binder include hydrophilic or hydrophobic polymers, such as hydroxyethyl cellulose (HEC), hydroxypropyl methyl cellulose (HPMC), carboxymethyl cellulose (CMC), sodium polyacrylate (SPA), and fluorine-based polymers (polytetrafluoroethylene (PTFE)). The content of the binder may be 0.01 to 5 parts by mass relative to 100 parts by mass of the positive electrode active material. Examples of the conductive agent include cobalt compounds (metallic cobalt, cobalt oxide, cobalt hydroxide, etc.). The content of the conductive agent may be 1 to 20 parts by mass relative to 100 parts by mass of the positive electrode active material. Examples of the expansion inhibitor include zinc oxide. The content of the expansion inhibitor may be 0.01 to 5 parts by mass relative to 100 parts by mass of the positive electrode active material.
[0053] The zinc battery according to the present embodiment can include an electrolyte, and includes, for example, a battery case, an electrode group (for example, an electrode plate group), and an electrolyte. The electrode group and the electrolyte are contained in the battery case. The electrode group includes a negative electrode, a positive electrode, and a separator.
[0054] Examples of the material of the separator include organic materials (resin materials, etc.) and inorganic materials. Examples of the resin material include polyamide-based polymers (e.g., polyamide), olefin-based polymers (e.g., polyolefins such as polyethylene and polypropylene), and nylon-based polymers (e.g., nylon). Examples of the inorganic material include oxides such as alumina, titania, and silicon dioxide; nitrides such as aluminum nitride and silicon nitride; and sulfates such as barium sulfate and calcium sulfate. The separator may be an ion-exchange resin membrane, a cellophane-based recycled resin membrane, an inorganic-organic separator, a polyolefin-based nonwoven fabric, and the like. Examples of the manufacturing method of the separator include a wet method (phase separation method), a dry method (stretching and perforating method), melt blowing, and electrospinning. From the viewpoint of easily obtaining excellent life performance, the separator may contain polyolefin, may contain at least one selected from the group consisting of polyethylene and polypropylene, and may contain polyethylene.
[0055] From the viewpoint of hydrophilization, the separator may contain an anionic surfactant, a cationic surfactant, an amphoteric surfactant, a nonionic surfactant, etc., and may be surface-treated by surfactant treatment, sulfonation treatment, fluorine gas treatment, acrylic acid graft polymerization treatment, corona discharge treatment, plasma treatment, etc. By being hydrophilized, the separator becomes more compatible with the electrolyte, and a sufficient current density is easily obtained.
[0056] The electrolytic solution contains, for example, a solvent and an electrolyte. Examples of the solvent include water (e.g., ion-exchanged water). Examples of the electrolyte include basic compounds, such as alkali metal hydroxides, such as potassium hydroxide (KOH), sodium hydroxide (NaOH), and lithium hydroxide (LiOH). From the viewpoint of easily obtaining excellent life performance, the electrolytic solution may contain an alkali metal hydroxide or may contain potassium hydroxide. The zinc battery according to this embodiment can be used as an alkaline zinc battery using an alkaline electrolyte.
[0057] As the content of the alkali metal hydroxide or the content of the potassium hydroxide, the content C3 may be in the following range based on the total amount of the electrolyte. From the viewpoint of easily obtaining excellent life performance, the content C3 may be 20 mol / L or less, 15 mol / L or less, 12 mol / L or less, 10 mol / L or less, 9 mol / L or less, 8 mol / L or less, 7 mol / L or less, or 6 mol / L or less. From the viewpoint of easily obtaining excellent high-rate discharge performance, the content C3 may be 1 mol / L or more, 3 mol / L or more, 5 mol / L or more, 6 mol / L or more, 7 mol / L or more, or 8 mol / L or more. From these viewpoints, the content C3 may be 1 to 20 mol / L, 1 to 10 mol / L, 1 to 8 mol / L, 1 to 7 mol / L, 1 to 6 mol / L, 4 to 20 mol / L, 4 to 10 mol / L, 4 to 8 mol / L, 4 to 7 mol / L, 4 to 6 mol / L, 6 to 20 mol / L, 6 to 10 mol / L, 6 to 8 mol / L, 6 to 7 mol / L, 7 to 20 mol / L, 7 to 10 mol / L, 7 to 8 mol / L, 8 to 20 mol / L, or 8 to 10 mol / L.
[0058] The electrolytic solution may contain components other than the solvent and the electrolyte, such as boric acid, sodium borate, potassium phosphate, potassium fluoride, potassium carbonate, sodium phosphate, sodium fluoride, sodium hydroxide, lithium hydroxide, zinc oxide, antimony oxide, titanium dioxide, a nonionic surfactant, an anionic surfactant, and the like.
[0059] A manufacturing method for a zinc battery (e.g., a nickel-zinc battery) according to this embodiment includes, for example, an electrode manufacturing process for obtaining electrodes (negative electrode and positive electrode) and an assembly process for assembling components including the negative electrode to obtain a zinc battery.
[0060] In the electrode manufacturing process, electrodes (negative and positive electrodes) are manufactured. For example, a solvent (e.g., water) is added to the raw materials of the electrode materials (negative and positive electrode materials) and kneaded to obtain an electrode material paste (a paste-like electrode material), and then the electrode material paste is used to form an electrode material layer.
[0061] The raw materials for the negative electrode material include raw materials for the negative electrode active material (e.g., zinc metal, zinc oxide, and zinc hydroxide), additive A, other additives (e.g., binders), etc. The raw materials for the positive electrode material include raw materials for the positive electrode active material (e.g., nickel hydroxide), additives (e.g., binders), etc.
[0062] As a method for forming the electrode material layer, for example, an electrode material paste may be applied or filled onto a current collector, and then dried to obtain an electrode material layer. The density of the electrode material layer may be increased by pressing or the like, as necessary.
[0063] In the assembly process, for example, the negative electrodes and positive electrodes obtained in the electrode manufacturing process are alternately stacked with separators interposed therebetween, and the negative electrodes and the positive electrodes are connected with straps to form an electrode group. Next, the electrode group is placed in a battery case, and a lid is attached to the top surface of the battery case to obtain an unformed zinc battery.
[0064] Next, the electrolyte is poured into the battery case of the unformed zinc battery, and then the battery is left for a certain period of time. Next, the zinc battery is formed by charging the battery under predetermined conditions. The formation conditions can be adjusted according to the properties of the electrode active materials (negative and positive active materials).
[0065] Although the embodiment of the present disclosure has been described above, the present disclosure is not limited to the above embodiment.For example, in the above embodiment, an example of a nickel-zinc battery (e.g., a nickel-zinc secondary battery) in which the positive electrode is a nickel electrode has been described, but the zinc battery may be an air-zinc battery (e.g., an air-zinc secondary battery) in which the positive electrode is an air electrode, or a silver-zinc battery (e.g., a silver-zinc secondary battery) in which the positive electrode is a silver oxide electrode.
[0066] The air electrode of the air zinc battery can be a known air electrode used in air zinc batteries. The air electrode includes, for example, an air electrode catalyst, an electron conductive material, etc. The air electrode catalyst can be an air electrode catalyst that also functions as an electron conductive material.
[0067] As the air electrode catalyst, one that functions as a positive electrode in an air zinc battery can be used, and various air electrode catalysts that can utilize oxygen as a positive electrode active material can be used. Examples of the air electrode catalyst include carbon-based materials (graphite, etc.) having an oxidation-reduction catalytic function, metal materials (platinum, nickel, etc.) having an oxidation-reduction catalytic function, and inorganic oxide materials (perovskite-type oxides, manganese dioxide, nickel oxide, cobalt oxide, spinel oxide, etc.) having an oxidation-reduction catalytic function. The shape of the air electrode catalyst is not particularly limited, and may be, for example, particulate. The content of the air electrode catalyst in the air electrode may be 5 to 70 volume % with respect to the total amount of the air electrode.
[0068] As the electron conductive material, a material that has electrical conductivity and enables electron conduction between the air electrode catalyst and the separator can be used. Examples of the electron conductive material include carbon blacks such as ketjen black, acetylene black, channel black, furnace black, lamp black, and thermal black; graphites such as natural graphite such as flake graphite, artificial graphite, and expanded graphite; conductive fibers such as carbon fibers and metal fibers; metal powders such as copper, silver, nickel, and aluminum; organic electron conductive materials such as polyphenylene derivatives; and any mixtures thereof. The shape of the electron conductive material may be particulate or other shapes. The electron conductive material may be used in a form that provides a continuous phase in the thickness direction in the air electrode. For example, the electron conductive material may be a porous material. The electron conductive material may be in the form of a mixture or complex with the air electrode catalyst, and may be an air electrode catalyst that also functions as an electron conductive material as described above. The content of the electron conductive material in the air electrode may be 10 to 80% by volume with respect to the total amount of the air electrode.
[0069] As the silver oxide electrode of the silver-zinc battery, a known silver oxide electrode used in silver-zinc batteries can be used. The silver oxide electrode includes, for example, silver(I) oxide. EXAMPLES
[0070] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to the following examples.
[0071] <Preparing the zinc battery> A zinc battery having the characteristics shown in Table 1 was fabricated by the following procedure.
[0072] Example 1 [Preparation of negative electrode] Zinc oxide A (manufactured by Nacalai Tesque, Inc., product name: zinc oxide, primary particle shape: hexagonal columnar, number average particle diameter: 600 nm, BET specific surface area: 2.26 m 2 / g, tap density 0.700g / cm 3 90.6 parts by mass of zinc oxide, 1.5 parts by mass of polytetrafluoroethylene (PTFE), 2 parts by mass of lead oxide, 5 parts by mass of acetylene black, 0.9 parts by mass of polysorbate 80 (manufactured by Thermo Fisher Scientific Co., Ltd., trade name: Polysorbate 80, polyoxyethylene sorbitan monooleate (also known as polyoxyethylene sorbitan monooleate ester), HLB value: 13.0 to 15.7, number of moles of ethylene oxide added: 20), and water were mixed to obtain a negative electrode material composition (negative electrode material paste) having a solid content concentration of 73.9% by mass. The content of polysorbate 80 was 1.0 part by mass relative to 100 parts by mass of zinc oxide (negative electrode active material). This negative electrode material composition was mixed in a planetary mixer at 2000 rpm for 5 minutes to obtain a block negative electrode material composition. The aggregated negative electrode material composition was stretched through a 0.650 mm gap in a roll press machine several times, and then stretched by adjusting the gap of the roll press to obtain an anode material layer having a thickness of 1.2 mm. The anode material layer was cut to obtain a rectangular anode material sheet having a size of 20 mm x 20 mm.
[0073] Next, a 20 mm x 23 mm copper wire mesh with 100 mesh was prepared as a negative electrode current collector, and the above-mentioned negative electrode material sheet was attached to the negative electrode current collector. Then, after molding using a roll press machine with the roll distance adjusted to 1.3 mm, a copper lead with a thickness of 100 μm and a width of 3 mm was welded to the exposed part of the negative electrode current collector to form a current extraction part, thereby producing a negative electrode with a total thickness of 1.2 mm.
[0074] [Preparation of positive electrode] 89.8 parts by mass of nickel hydroxide, 0.2 parts by mass of carboxymethylcellulose (CMC), 5 parts by mass of cobalt monoxide, 5 parts by mass of tricobalt tetroxide, and water were mixed to obtain a positive electrode material composition (positive electrode material paste) with a solid content concentration of 75% by mass. This positive electrode material composition was mixed for 5 minutes at 2000 rpm in a rotary mixer. After adding 0.9 parts by mass of PTFE to 100 parts by mass of the above-mentioned nickel hydroxide, the mixture was mixed at 2000 rpm for 30 seconds to obtain a mixture. This mixture was filled into a 2 mm thick foamed nickel (porosity 27%) so that an uncoated portion was formed in a part. After drying at 80°C for 1 hour, the thickness was adjusted to 1 mm by a roll press to obtain a sheet. This sheet was cut to obtain an electrode having a square positive electrode material layer forming portion of 25 mm x 25 mm and a collector (foamed nickel) exposed portion with a width of 3 mm. Two of these electrodes were stacked and integrated by roll pressing, and a nickel lead 100 μm thick and 3 mm wide was welded to the exposed part of the current collector to form a current extraction part, producing a positive electrode with a total thickness of 2 mm. The part of the positive electrode other than the current extraction part was wrapped in a bag-like shape with a nonwoven fabric 120 μm thick to obtain a positive electrode body.
[0075] [Preparation of electrolyte] An alkaline solution was prepared by dissolving powdered potassium hydroxide (KOH) in pure water to a concentration of 8 mol / L (based on the total amount of the electrolyte). An excess amount of powdered zinc oxide (ZnO) was added to this alkaline solution, and the solution was stirred at 25°C for 24 hours. The solution was then filtered to remove the excess zinc oxide, producing an electrolyte.
[0076] [Creating a zinc battery] As a separator, a porous membrane (manufactured by Ube Industries, Ltd., product name: UP3355) was hydrophilized with a surfactant (manufactured by Sigma-Aldrich Japan, LLC, product name: Triton (registered trademark)-X100). The hydrophilization was performed by immersing the porous membrane in an aqueous solution containing 1% by mass of Triton-X100 for 24 hours, and then drying at 25 ° C. for 1 hour. The above-mentioned negative electrode and positive electrode body were stacked with the separator in between to obtain an electrode body. Next, two polypropylene sheets molded to 35 mm x 60 mm were stacked, and three sides were welded in a bag shape to form an exterior body, and then the electrode body was inserted into the interior of the exterior body. Then, the exterior body containing the electrode body was sandwiched from both sides between two acrylic plates of 50 mm x 50 mm x 8 mm, and the four corners were screwed. After that, 4.5 mL of the above-mentioned electrolyte was injected into the exterior body and vacuum impregnated, and then the one side of the exterior body that was not welded was sealed to produce an unformed zinc battery (nickel-zinc battery).Then, at 25°C, the battery was charged at a constant current of 32 mA (0.05 C) until it reached 320 mAh (SOC 50%), and then discharged at a constant current of 32 mA (0.05 C) until the battery voltage reached 1.4 V, producing a formed zinc battery (nominal capacity: 640 mAh).
[0077] Example 2 In preparing the negative electrode, zinc oxide A was mixed with zinc oxide B (a mixture containing zinc oxide and polysorbate 80 (polyoxyethylene sorbitan monooleate (also known as polyoxyethylene sorbitan monooleate), HLB value: 13.0 to 15.7, number of moles of ethylene oxide added: 20), without adding 0.9 parts by mass of polysorbate 80 (manufactured by Thermo Fisher Scientific Co., Ltd., product name: Polysorbate 80), content of polysorbate 80: 2.4 to 3.0 parts by mass per 100 parts by mass of zinc oxide (negative electrode active material), manufactured by Sakai Chemical Industry Co., Ltd., product name: CANDY ZINC 1000, plate-like accumulated spherical zinc oxide, primary particle shape: plate-like, particle diameter: 947 nm, BET specific surface area: 8.50 m) 2 / g, tap density 0.715g / cm 3 A zinc battery was produced in the same manner as in Example 1, except that the above-mentioned was changed to the above-mentioned.
[0078] Example 3 A zinc battery was produced in the same manner as in Example 1, except that polysorbate 20 (manufactured by Thermo Fisher Scientific Co., Ltd., product name: Polysorbate 20, polyoxyethylene sorbitan monolaurate (also known as polyoxyethylene sorbitan monolaurate ester), HLB value: 16.7 to 17.0, number of moles of ethylene oxide added: 20) was used instead of polysorbate 80. The content of polysorbate 20 was 1.0 part by mass relative to 100 parts by mass of zinc oxide (negative electrode active material).
[0079] Example 4 A zinc battery was produced in the same manner as in Example 1, except that polysorbate 60 (manufactured by Thermo Fisher Scientific Co., Ltd., product name: Polysorbate 60, polyoxyethylene sorbitan monostearate (also known as polyoxyethylene sorbitan monostearate ester), HLB value: 14.9 to 15.7, number of moles of ethylene oxide added: 20) was used instead of polysorbate 80. The content of polysorbate 60 was 1.0 part by mass relative to 100 parts by mass of zinc oxide (negative electrode active material).
[0080] Example 5 A zinc battery was produced in the same manner as in Example 1, except that polysorbate 65 (manufactured by Thermo Fisher Scientific Co., Ltd., product name: Polysorbate 65, polyoxyethylene sorbitan tristearate (also known as polyoxyethylene sorbitan tristearate), HLB value: 10.5 to 10.7, number of moles of ethylene oxide added: 20) was used instead of polysorbate 80. The content of polysorbate 65 was 1.0 part by mass relative to 100 parts by mass of zinc oxide (negative electrode active material).
[0081] Example 6 A zinc battery was produced in the same manner as in Example 1, except that sorbitan was used instead of polysorbate 80. The content of sorbitan was 1.0 part by mass with respect to 100 parts by mass of zinc oxide (negative electrode active material).
[0082] Example 7 A zinc battery was produced in the same manner as in Example 1, except that sorbitol was used instead of polysorbate 80. The content of sorbitol was 1.0 part by mass with respect to 100 parts by mass of zinc oxide (negative electrode active material).
[0083] Example 8 A zinc battery was produced in the same manner as in Example 1, except that erythritol was used instead of polysorbate 80. The content of erythritol was 1.0 part by mass with respect to 100 parts by mass of zinc oxide (negative electrode active material).
[0084] Example 9 A zinc battery was produced in the same manner as in Example 1, except that maltitol was used instead of polysorbate 80. The content of maltitol was 1.0 part by mass with respect to 100 parts by mass of zinc oxide (negative electrode active material).
[0085] Comparative Example 1 A zinc battery was produced in the same manner as in Example 1, except that polysorbate 80 was not used in producing the negative electrode.
[0086] Example 10 A zinc battery was prepared in the same manner as in Example 1, except that the content of polysorbate 80 per 100 parts by mass of zinc oxide (negative electrode active material) was changed to 0.5 parts by mass, and the concentration of potassium hydroxide in the electrolyte was changed to 6 mol / L when preparing the electrolyte.
[0087] Example 11 A zinc battery was produced in the same manner as in Example 1, except that the concentration of potassium hydroxide in the electrolyte was changed to 6 mol / L when preparing the electrolyte. The content of polysorbate 80 was 1.0 part by mass per 100 parts by mass of zinc oxide (negative electrode active material).
[0088] Example 12 A zinc battery was prepared in the same manner as in Example 1, except that the content of polysorbate 80 was changed to 2.0 parts by mass per 100 parts by mass of zinc oxide (negative electrode active material), and the concentration of potassium hydroxide in the electrolyte was changed to 6 mol / L when preparing the electrolyte.
[0089] Comparative Example 2 A zinc battery was produced in the same manner as in Example 1, except that no polysorbate 80 was used in producing the negative electrode, and the concentration of potassium hydroxide in the electrolyte was changed to 6 mol / L in producing the electrolyte.
[0090] <Evaluation of life performance> At 40°C, the above zinc battery was subjected to a test in which the following charge and discharge operations were one cycle, and the discharge capacity of each cycle was measured. Then, the capacity retention rate (%) (=[B / A]×100) of the discharge capacity B at the 120th cycle to the discharge capacity A at the first cycle was calculated. As shown in Table 1, the capacity retention rate was 48% in Example 1, 63% in Example 2, 46% in Example 3, 48% in Example 4, 48% in Example 5, 48% in Example 6, 47% in Example 7, 46% in Example 8, 45% in Example 9, 27% in Comparative Example 1, 33% in Example 10, 54% in Example 11, 71% in Example 12, and 25% in Comparative Example 2. Charge at a constant current of 128mA (0.2C) until the battery capacity reaches 320mAh (SOC50%) (However, if the battery voltage reaches 2.1V before the battery capacity reaches 320mAh, charge until the battery voltage reaches 2.1V) Discharge at a constant current of 128mA (0.2C) until the battery voltage reaches 1.0V
[0091] [Table 1]
Claims
1. A negative electrode current collector and a negative electrode material supported on the negative electrode current collector, The negative electrode material comprises a negative electrode active material containing zinc, and at least one additive selected from the group consisting of sorbitan compounds and sugar alcohol compounds.
2. 2. The negative electrode for a zinc battery according to claim 1, wherein the additive comprises a polyoxyalkylene sorbitan fatty acid ester.
3. 3. The zinc battery negative electrode according to claim 2, wherein the polyoxyalkylene sorbitan fatty acid ester has an HLB value of 9.0 or more.
4. 2. The zinc battery negative electrode of claim 1, wherein the additive comprises sorbitan.
5. 2. The zinc battery negative electrode of claim 1, wherein the additive comprises a sugar alcohol.
6. The zinc battery negative electrode according to claim 1, wherein the content of the additive is 0.1 to 10 parts by mass per 100 parts by mass of the negative electrode active material.
7. A zinc battery comprising the zinc battery negative electrode according to any one of claims 1 to 6 and a positive electrode.
Citation Information
Patent Citations
Nickel zinc battery
JP1983126665A